Postoperative evaluation of posterior tibial tendon transfer: an alternative for cases of drop-foot - Vieira, Larissa Miranda Xavier; Fleury, Rodrigo Barra Caiado; Nunes, Bruno Severino; Martins, Jefferson Soares; Costa, Edegmar Nunes (Scientific Journal of the Foot & Ankle, 2018)
Objectives: To analyse and report the advantages of posterior tibial tendon transfer amongst patients with drop-foot as well as evaluate the degrees of foot biomechanical restoration and patient quality of life improvement. Methods: Seven patients diagnosed with drop-foot received surgery in which the posterior tibial tendon was transferred via the syndesmotic membrane, and the tendon was fixed to the lateral cuneiform bone using an interference screw. Results: The patients completed the Stanmore questionnaire before and after surgery to report their improvements with regard to all of the questionnaire criteria. Conclusion: The adopted surgical technique is an effective method of disease correction, with associated pain improvement, resumption of wearing shoes, elimination of the regular use of an ankle-foot orthosis (AFO), muscle strength gain, and functional capacity improvement. Level of Evidence IV; Therapeutic Study; Case Series.